COMPARISON OF EFFICACY OF 10% POTASSIUM HYDROXIDE SOLUTION VERSUS CRYOTHERAPY IN TREATMENT OF MOLLUSCUM CONTAGIOSUM - Qureshi, Asfandyar; Zeb, Mahwish; Jalal-ud-din, Mir; Sheikh, Zafar Iqbal; Alam, Muhammad Adeel; Anwar, Syed Abbas (Journal of Ayub Medical College Abbottabad, 2016)
Background: Different topical therapies are being used for treating molluscum contagiosum. Potassium hydroxide in varying solution strengths with irritant reaction on the skin can help in eliminating the infection. It is cheap, easily available, can be easily applied at home, with good safety profile and cost effectiveness. This study was conducted to compare the efficacy of 10% potassium hydroxide solution versus cryotherapy in treating molluscum contagiosum. Methodology: This study was a Randomized control trial conducted in the Department of dermatology, Military hospital Rawalpindi. Study included 120 randomly selected patients with molluscum contagiosum divided equally into two groups. Group A were treated with 10% potassium hydroxide aqueous solution applied daily to the lesions twice daily for 6 weeks while Group B received weekly cryotherapy with liquid nitrogen. The status of lesions was documented weekly for 6 weeks. Results: Of the 120 patients enrolled, 67 (55.8%) were male and 53 (44.2%) were female. Mean age of patients was 20.53(±8.17) years. At base line Molluscum contagiosum lesion ranged from minimum of 2 lesions to maximum of 26 lesions with a mean of 8.95 (SD ±4.45) lesions. Of 120 patients, complete clearance was observed in 98(81.6%) of patients, 48(80%) patients had lesion clearance in Group A and 50 (83.3%) patients had lesion clearance was observed in Group B. No statistical significance was observed in the lesion clearance between the two groups (p-0.63). Conclusion: The efficacy of 10% potassium hydroxide solution and cryotherapy is statistically same over 6 weeks of treatment. Thus less expensive, easily available and cosmetically more acceptable potassium hydroxide solution can be used instead of cryotherapy in treating molluscum contagiosum. Keywords: Molluscum contagiosum, cryotherapy, potassium hydroxide, efficacy